Analysis of the Application of Cooperation Principles in the Close the Door Youtube Channel Dialogue Entitled â€œKaesang Pangarep, Bongkar-Bongkaranâ€: A Pragmatic Review - Dwi Silva Oktarina; Intan Sari Ramdhani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
As social beings, humans always use language in communicating. All areas of life that include what is experienced and felt in everyday life require language to express so that communication can arrive effectively and efficiently whether it is written or spoken. Currently, podcasts are very popular with the public because the news that is packaged is very interesting, easy to understand, and up to date. The podcast contains conversations that contain information in the form of speech. One area of pragmatics is speech. Close the door is a podcast that contains interviews with guest stars. There are various questions raised by the interviewer or Dedi Corbuzier directly. On the Youtube channel there are several interesting topics to analyze, one of which is entitled "Kaesang Pangarep, Bongkar-Bongkaran". The podcast contains interesting stories to analyze.